2005
DOI: 10.4049/jimmunol.175.9.6058
|View full text |Cite
|
Sign up to set email alerts
|

MARCO Is the Major Binding Receptor for Unopsonized Particles and Bacteria on Human Alveolar Macrophages

Abstract: Alveolar macrophages (AMs) avidly bind and ingest inhaled environmental particles and bacteria. To identify the particle binding receptor(s) on human AMs, we used functional screening of anti-human AM hybridomas and isolated a mAb, PLK-1, which inhibits AM binding of unopsonized particles (e.g., TiO2, latex beads; 63 ± 5 and 67 ± 4% inhibition, respectively, measured by flow cytometry; n = 11) and unopsonized bacteria (∼84 and 41% inhibition of Escherichia coli and Staphylococcus aureus binding by mAb PLK-1, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
151
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 185 publications
(169 citation statements)
references
References 45 publications
10
151
1
2
Order By: Relevance
“…The MARCO receptor binds environmental particles, bacteria, and oxidized lipids. 33,[47][48][49] The absence of MARCO leads to an increased inflammatory response suggesting MARCO modulates the immune response. 50,51 In lung alveolar macrophages increased MARCO expression polarized lung alveolar macrophages toward a profibrotic M2 phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…The MARCO receptor binds environmental particles, bacteria, and oxidized lipids. 33,[47][48][49] The absence of MARCO leads to an increased inflammatory response suggesting MARCO modulates the immune response. 50,51 In lung alveolar macrophages increased MARCO expression polarized lung alveolar macrophages toward a profibrotic M2 phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding this process is important for designing future biomaterials for applications such as drug delivery systems targeting specific receptors [31]. Hitherto, most related studies have been focused on inhalable natural particles [32,33] and metallic bone substitutes [34,35]. In our investigation, we attempted to screen for some of the receptors that were previously shown to associate with biomaterial degradation and might be involved in scaffold degradation.…”
Section: Receptors Involved In Scaffold Degradationmentioning
confidence: 99%
“…1 Several scavenger receptors have also been identified that directly interact with nonopsonized particles, and these are broadly classified as class A (macrophage receptor with collagenous structure) and class B (2 transmembrane receptors), 2 whereas among others is the C-type lectin-like receptor, dectin-1. [3][4][5][6][7][8][9] Assays for these scavenger receptors use nonselective inhibitors, polyinosinic acid, liposomes containing phosphatidylserine, oxidized low-density lipoprotein, or fucoidan, to inhibit this pathway. Phagocytosis of particles is accompanied by major rearrangements in the actin-myosin cytoskeleton, but there is little information on how scavenger receptors interact with proteins of the cytoskeleton.…”
Section: Introductionmentioning
confidence: 99%